DNA Barcoding and Phylogenetic Characterization of Mushrooms with in the Adirondack Park - Elwess, Nancy L.; Leverea, Siobhan; Latourellea, Sandra M. (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
In recent years, fungal identification has risen in popularity. It is often difficult to identify mushrooms using the morphologically-based identification system, due to extreme similaritiesbetween species. There are also notable differences in species at a mature stage versus a young fruiting body. The internal transcribed spacer (ITS) of nuclear DNA has been used for over 15years as a focus when analyzing fungal diversity. Only recently has ITS been deemed as the official marker used in fungal DNA barcoding. The Adirondack Park is a region consisting of 6 millionacres of “forever wild” terrain. This hosts over 3000 lakes and ponds and 30,000 miles of streamsand rivers in the heart of its boreal forests. Mushroom sampling was performed within this region. The DNA was isolated, amplified, and sequenced,using ITS6 and ITS8 primers.Ultimately, all DNA sequences were uploaded into an international DNA database.